A descriptive analysis of alcohol behaviors across gender subgroups within a sample of transgender adults. (January 2018) - Staples, Jennifer M.; Neilson, Elizabeth C.; George, William H.; Flaherty, Brian P.; Davis, Kelly Cue
Abstract: Objective: Transgender (trans) adults are identified as an at-risk group for problem alcohol use. Descriptive empirical data examining alcohol behaviors among trans adults is limited. The present study investigates alcohol behaviors – quantity, frequency, alcohol-related problems, and drinking to cope motives – across sex assigned at birth, gender expression, and gender identity subgroups within a sample of trans adults. Method: A total of 317 trans participants were recruited to complete a cross-sectional battery of online measures assessing alcohol use behaviors, alcohol-related problems, and drinking to cope. Gender identity was assessed through two methods: (1) an open-ended question in which participants wrote-in their primary gender identity; and (2) participants rated the extent to which they identified with 14 gender identity categories. Results: This sample had high rates of alcohol use, alcohol-related problems, and drinking to cope motives relative to the general population. Significant and meaningful differences in drinking frequency, alcohol-related problems and drinking motives were found according to gender expression, but not sex assigned at birth or gender identity. Conclusions: Future work should examine alcohol behaviors among trans individuals, including investigation of predictors and causal pathways, to inform prevention and intervention work aimed at reducing trans people's risk for alcohol-related problems. Highlights: Trans adults report more hazardous alcohol use compared to the general population. There were no differences in alcohol use behaviors across different gender identities. Gender expression and passing as cisgender were associated with differential alcohol use behaviors. The majority of trans adults reported drinking to cope at least some of the time. Future work should examine trans adults' experiences with discrimination, coping motives, and alcohol use behaviors.